1997
DOI: 10.1021/ac9607525
|View full text |Cite
|
Sign up to set email alerts
|

Selective Determination of Cr(VI) by a Self-Assembled Monolayer-Based Electrode

Abstract: We have developed a selective electrode for chromium(VI), based on a self-assembled monolayer of 4-(mercapto-n-alkyl)pyridinium on gold surfaces, which exhibits unique speciation capabilities. Cr(VI) levels as low as 1 parts per trillion can be detected using a 4-(mercaptoethyl)pyridinium monolayer. The different parameters that govern the analytical performance of these electrodes have been studied in detail and optimized. In addition, the organization of the monolayers has been examined by a variety of surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
161
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(166 citation statements)
references
References 33 publications
5
161
0
Order By: Relevance
“…Two types of working electrodes were employed. Glassy carbon electrodes (GC, 3 mm diameter, Atomergic Chemetals, Farmingdale, NY) were constructed and polished prior to film deposition following a previously described procedure [44]. Indium-tin-oxide (ITO) plates (area 0.7 cm À 2 , surface conductivity; < 10 W/Square), Delta Technologies, Stillwater, MN) were washed with pure water, ethanol and finally dried at room temperature for 1 ± 2 h before use.…”
Section: Instrumentsmentioning
confidence: 99%
“…Two types of working electrodes were employed. Glassy carbon electrodes (GC, 3 mm diameter, Atomergic Chemetals, Farmingdale, NY) were constructed and polished prior to film deposition following a previously described procedure [44]. Indium-tin-oxide (ITO) plates (area 0.7 cm À 2 , surface conductivity; < 10 W/Square), Delta Technologies, Stillwater, MN) were washed with pure water, ethanol and finally dried at room temperature for 1 ± 2 h before use.…”
Section: Instrumentsmentioning
confidence: 99%
“…For example, Rubinstein and coworkers [7~9] demonstrated that mixed functionalized SAMs could recognize copper ions selectively in the presence of other ions. Mandler and co-workers [10,11] have reported a highly sensitive electrode for cadmium ions and chromium(VI) ions using self-assembled monolayers-based electrodes. S.Berchmans et al [12] studied the formation of nickel hydroxide monolayers on Au through a SAMs, J.Y.Mo [13] presented a method for the determination of dopamine and epinephrine by SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical methods commonly used for the determination of Cr(VI) are atomic absorption spectrometry (AAS) [9], fluorescence spectrometry [10], and electrochemical measurements [11]. If these analytical methods are combined with the microextraction of pine needle powder for the determination of Cr(VI), the sensitivity and selectivity must be increased, and the detection of limit must be decreased.…”
Section: Introductionmentioning
confidence: 99%